SOSIALISASI PENERAPAN STANDAR SNI 02-2406:1991 DAN SNI 03-3424:1994 DALAM PERENCANAAN DRAINASE PERKOTAAN WILAYAH KABUPATEN KARANGANYAR - Kurnianingsih, Oktavia; Hadiani, Rr Rintis; Utomo, Budi; Rifai, Muji; Solichin , Solichin (Universitas Mataram, 2024)
Karanganyar Regency is one of the regencies located in Central Java. The Karanganyar Regency area is located in a mountainous area to a plain area. Urban Karanganyar Regency has experienced an increase in population, causing a reduction in absorption areas to be built up. Development in urban areas always increases as a support for facilities and infrastructure. Urban drainage is one of the important facilities and infrastructures in urban areas to regulate water disposal. Increased urbanization causes inundation and flooding. The problem of urban inundation causes many losses. Overcoming problems in Karanganyar District, the purpose of this service together with partners is to socialize the application of SNI 02-2406: 1991 and SNI 03-3424: 1994 in urban drainage planning as flood mitigation. The method used is through socialization of urban drainage planning material and direct question and answer discussions with participants and pretest and post tests related to drainage planning. Prior to the socialization, a survey of drainage channel conditions including dimensions, sedimentation and debris and drainage flow direction was conducted. The results obtained from this activity are the increased ability of participants in optimal urban drainage planning. This community service activity is able to provide an understanding of the importance of maintaining drainage channels from garbage and sedimentation. This community service activity is able to provide an understanding of the importance of maintaining drainage channels from garbage and sedimentation. The community and government can be directly involved in urban and sustainable drainage management.